Investigating the Effects of Annealing on the Mechanical Properties of FFF-Printed Thermoplastics - Javaid Butt; Raghunath Bhaskar (Journal of Manufacturing and Materials Processing, 2020)
Fused filament fabrication (FFF) is a cost-effective additive manufacturing method that makes use of thermoplastics to produce customised products. However, there are several limitations associated with FFF that are adversely affecting its growth including variety of materials, rough surface finish and poor mechanical properties. This has resulted in the development of metal-infused thermoplastics that can provide better properties. Furthermore, FFF-printed parts can be subjected to post-processes to improve their surface finish and mechanical properties. This work takes into consideration two commonly used polymeric materials, i.e., ABS (acrylonitrile butadiene styrene) and PLA (polylactic acid) and compares the results with two metal-infused thermoplastics i.e., copper-enhanced PLA and aluminium-enhanced ASA (acrylonitrile styrene acrylate). The four different materials were subjected to a post-process called annealing to enhance their mechanical properties. The effect of annealing on these four materials was investigated through dimensional analysis, ultrasonic testing, tensile testing, microstructural analysis and hardness testing. The results showed that annealing affects the materials differently. However, a correlation among ultrasonic testing, tensile testing and microstructural analysis was observed for all the materials based on their crystallinity. It was found that the semi-crystalline materials (i.e., PLA and copper enhanced PLA) showed a considerable increase in tensile strength post-annealing. However, the amorphous materials (ABS and aluminium-enhanced ASA) showed a comparatively lower increase in tensile strength, demonstrating that they were less receptive to annealing. These results were supported by higher transmission times and a high percentage of voids in the amorphous materials. The highest hardness values were observed for the ASA material and the lowest for the ABS material. This work provides a good comparison for the metal-infused thermoplastics and their applicability with the commonly used PLA and ABS materials.